A review of microbial electrosynthesis applied to carbon dioxide capture and conversion: The basic principles, electrode materials, and bioproducts. Issue 51 (September 2021) - Zhang, Shixuan; Jiang, Jiwei; Wang, Haonan; Li, Fengxiang; Hua, Tao; Wang, Wei
Highlights: Microbial electrosynthesis could mitigate greenhouse effect while synthesizing bioproducts. The basics of bioelectrochemical system and features of pure/mixed cultures were discussed. Common-used electrode materials with their advantages and disadvantages were illustrated. Plentiful bio-products from CO2 via microbial electrosynthesis were proposed systematically. Abstract: Atmospheric carbon dioxide (CO2 ) concentrations are currently rising at an unstoppable rate, and it is urgent to curb this trend for a stable and sustainable atmospheric environment. Under this adverse situation, microbial electrosynthesis (MES) applied to CO2 capture and conversion has received increasing attention in recent years for mitigating greenhouse effects while biosynthesizing higher-value products. Research on the CO2 capture and conversion in MES has been increasing in recent years, in 2020 alone, there has been more than 1400 papers concerning the bioelectrochemical CO2 capture and conversion. In this review, the basics of bioelectrochemical systems are first briefly summarized to provide an overall understanding about them. Then, several commonly used electrode materials such as carbonaceous materials, metallic materials, and carbonaceous-metallic materials, along with their advantages and disadvantages, are illustrated. Additionally, the features of pure/mixed cultures are discussed in this review. In particular, many biobased products obtained from CO2 conversion via MES are proposed systematically according to their respective carbon chain lengths. Finally, perspectives on how to improve the MES performance and enable this process to be more suitable and feasible for the industrialization of CO2 capture and conversion are presented here.